1997
DOI: 10.1162/jocn.1997.9.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric and Allocentric Constraints in the Expression of Patterns of Interlimb Coordination

Abstract: Tasks that are easy when performed in isolation become difficult when performed simultaneously in the upper and/or lower limbs. This observation points to basic CNS constraints in the organization of patterns of interlimb coordination. The present studies provide evidence for the existence of two basic coordinative constraints whose effects may be additive under certain conditions. On one hand, the egocentric constraint denotes a general preference for moving the limbs toward or away from the longitudinal axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
110
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 60 publications
17
110
1
Order By: Relevance
“…Consistent with our results, this kind of bimanual coordination task, i.e. in which homologous muscles are alternately engaged, has been shown to result in lower M1 activation compared to those in which homologous muscles are active simultaneously (Swinnen et al, 1997, Aramaki et al, 2006. This may be attributable to stronger involvement of the dominant motor cortex in ipsilateral hand movements via interaction with the non-dominant motor system, known as neural crosstalk.…”
Section: Bimanual Tasksupporting
confidence: 88%
“…Consistent with our results, this kind of bimanual coordination task, i.e. in which homologous muscles are alternately engaged, has been shown to result in lower M1 activation compared to those in which homologous muscles are active simultaneously (Swinnen et al, 1997, Aramaki et al, 2006. This may be attributable to stronger involvement of the dominant motor cortex in ipsilateral hand movements via interaction with the non-dominant motor system, known as neural crosstalk.…”
Section: Bimanual Tasksupporting
confidence: 88%
“…As hypothesized, the results generally confirmed the findings of previous research that clearly showed that accuracy and variability evolve monotonically between the different coordination modes (Buekers et al, 2000;Swinnen, Jardin, Meulenbroek, Dounskaia, & Hofkens-Van Den Brandt, 1997;Zaal et al, 2000). Specifically, the best synchronization performance was observed in the in-phase synchronization mode while the anti-phase mode involved significant performance loss.…”
Section: Accepted Manuscript Synchronization 27supporting
confidence: 89%
“…Brain activations in young and older adults were compared during the per-formance of isolated rhythmical hand/foot movements as well as during their coordination, whereby both limbs moved either in the same direction (isodirectional) or in opposite directions (nonisodirectional). Previous behavioral work has shown convincingly that nonisodirectional patterns are more difficult and are produced with lower accuracy and stability than isodirectional patterns in normal subjects (Baldissera et al, 1982(Baldissera et al, , 1991Kelso and Jeka, 1992;Carson et al, 1995;Serrien et al, 2000) and in Parkinson and stroke patients (Swinnen et al, 1997;Debaere et al, 2001b). Accordingly, the aforementioned conditions represented a gradient of complexity, ranging from isolated to coordinated limb movements of different difficulty levels.…”
Section: Introductionmentioning
confidence: 93%